MORAL EDUCATION ACCORDING TO IBN MISKAWAYH AND AL-GHAZALI - Abd Mukti; Amroeni Drajat; Mourssi Abbas Mourssi Hassan Kahwash (JURNAL TARBIYAH, 2021)
One of the most essential Islamic messages is to instill an excellent character to every human being, according to the guidance of the Prophet Muhammad (peace and blessings of Allah be upon him):  "Allah sent me to fulfill akhlaq (morals)". The fundamental message of Islam is to build akhlaq in human life. In Islam, a good character is known as Al-Akhlaq Al-Karimah. All Muslim thinkers do their research on Akhlaq or a good character. The research attempts to illustrate the concept of Al-Akhlaq Al-Karimah according to Ibn Miskawayh and Al-Ghazali and to describe their fundamental thoughts on the matter, explicitly dealing with the building of human character. The research is based on library research with a philosophical approach. From this study, I concluded that according to Ibn Meskavayh, look more philosopher while Al-Ghazali is more Sufistic. In the meantime, they have similarities to the fundamentals of the human faculty. Ibn Miskawayh and Al-Ghazaly had similarities to the basic human faculties, and this faculty should be preserved and developed. According to Ibn Miskawayh, the faculty of man should be educated by keeping all of these faculties always balanced in a way that he calls the middle way. This means that the human faculties must be balanced between over (Israf) and Distillation (Taqthir). The best of all is the middle thing. Al-Ghazali focuses his thoughts on building a good character on the Sufi approach to build a closer relationship with Almighty God through good and closer relationship to Almighty God.